Navigating and negotiating meanings of child abuse and neglect: Sociocultural contexts shaping Australian nurses' perceptions. (12th December 2019) - Lines, Lauren Elizabeth; Hutton, Alison; Grant, Julian Maree
Abstract: Nurses who work with children have the opportunity to make a difference by identifying and responding to child abuse and neglect. Little is known about the ways that nurses define, assess and respond to child abuse and neglect and how this subsequently affects children. This paper reports one of four themes identified through inductive analysis of a qualitative study exploring nurses' perceptions and experiences of keeping children safe from abuse and neglect. The aim of this paper was to report on how nurses understand and interpret child abuse, is found to be shaped by their own sociocultural contexts. A qualitative research design underpinned by social constructionism framed the study. Data were collected in 2016 and 2017 through 21 in‐depth, semi‐structured interviews with nurses who work with children in Australia. Key findings showed that nurses working with children had difficulty defining child abuse and drew upon multiple sources to construct a working definition. In addition to drawing from official legislation and guidelines, nurses compared and contrasted the level of abuse with their own personal and professional experiences of parenting. Nurses described the challenges of making assessments when faced with cultural practices different from their own. Nurses' descriptions of how they defined abuse showed that their assessments of child abuse and neglect were inextricably linked to their personal values and beliefs. As such, nurses were often working from their own value systems rather than consistently taking a child‐focussed approach. There was an absence of consistent and explicit critical reflection on ways that values and beliefs might shape practice at individual and system levels. We propose this is a missing aspect of child safe practice. Reflection on how personal and professional values and beliefs interact with the implementation of evidence‐informed approaches will increase nurses' capacity to maintain a child‐focus.